2016
DOI: 10.1017/s1751731115002566
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestion and fermentation characteristics of canola co-products simulate their digestion in the pig intestine

Abstract: Canola co-products are sources of amino acid and energy in pig feeds, but their fermentation characteristics in the pig intestine are unknown. Thus, we determined the in vitro fermentation characteristics of the canola co-products Brassica juncea solvent-extracted canola meal (JSECM), Brassica napus solvent-extracted canola meal (NSECM), B. napus expeller-pressed canola meal (NEPCM) and B. napus cold-pressed canola cake (NCPCC) in comparison with soybean meal (SBM). Samples were hydrolysed in two steps using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
0
22
1
1
Order By: Relevance
“…Thus, the differences in SID of AA for CPCC between studies could partly be attributed to differences in antinutritional factor content of CPCC, dietary level of CPCC, and method of estimating AA digestibility of CPCC. The IVDDM of CPCC (46%) was lower than the values that were reported by Woyengo et al (2016c) for solvent-extracted canola meal (63%), expeller-pressed canola meal (68%), and cold-pressed canola cake (70%), which could partly be attributed to the greater fiber content and TI activity in camelina co-products than in canola co-products.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Thus, the differences in SID of AA for CPCC between studies could partly be attributed to differences in antinutritional factor content of CPCC, dietary level of CPCC, and method of estimating AA digestibility of CPCC. The IVDDM of CPCC (46%) was lower than the values that were reported by Woyengo et al (2016c) for solvent-extracted canola meal (63%), expeller-pressed canola meal (68%), and cold-pressed canola cake (70%), which could partly be attributed to the greater fiber content and TI activity in camelina co-products than in canola co-products.…”
Section: Discussioncontrasting
confidence: 61%
“…The Lys to CP ratio (4.93%) of the CPPC was similar to the values (4.23% and 4.59%) that have been reported for camelina seed by (Almeida et al, 2013) implying that AA were not damaged during the production of CPCC from the camelina seed. The Lys to CP ratio in feedstuffs is an indicator of heat damage of AA in the same feedstuff during its thermal processing (Kim et al, 2012;Woyengo et al, 2015). TI, which reduces AA digestibility, is one of the antinutritive factors present in soybean and camelina products that limit the inclusion of these products in swine diets (Woyengo et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the DFM may have increased the nutrients digestibility in the upper part of the small intestine (as evidenced by increased VH:CD without increased feed intake), leading to reduced availability of the substrate for fermentation in the lower part of the small intestine and in the large intestine. Results from previous studies have shown reduced hindgut digestibility or fermentation as a result of an increase in the digestibility of nutrients in the small intestine by fiber-degrading enzyme supplementation ( Woyengo et al, 2016 ; Lee et al, 2018 ). Indeed, the DFM supplementation numerically reduced the cecal digesta concentration of the aforementioned VFA (acetic acid, propionic acid, and butyric acid) and significantly reduced the cecal digesta valeric acid concentration, which could support this aforementioned hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…The villous height to CD ratio (VH:CD) was calculated. Cecal digesta samples for VFA analysis were thawed and centrifuged and the resulting digesta fluid was prepared and analyzed for VFA (acetate, propionate, butyrate, and branched-chain VFA) as described by Woyengo et al (2016) . The pH in the ileum and cecum digesta were determined using a pH meter (AB 15; Fisher Scientific, Pittsburgh, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were observed by Chen et al [28] when the 2-step in-vitro gas production technique (2 + IVGPT) and 3 steps were used, the 2 + IVGPT method presented a significantly higher dietary fiber digestibility compared to the 3-step method. The 3-step method stimulated the hydrolysis of intestinal microbes, which was induced by fibrolytic enzymes mainly and not from fermentation [28,29]. In-vitro fermentation of different fiber treatments resulted in the production of short-chain fatty acids (SCFA), including acetic, propionic, and n-butyric acids that were measured.…”
Section: Discussionmentioning
confidence: 99%